2017
DOI: 10.5294/aqui.2017.17.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Distúrbio na imagem corporal: diagnóstico de enfermagem e características definidoras em pessoas ostomizadas

Abstract: Objetivo: identificar en la literatura las características definidoras del diagnóstico de enfermería disturbio en la imagen corporal en estudios desarrollados con personas ostomizadas. Métodos: se trata de una investigación bibliográfica, en la modalidad revisión integradora de la literatura, descriptiva y con enfoque cualitativo, realizada en noviembre del 2015, en las bases de datos Literatura Latinoamericana y del Caribe en Ciencias de la Salud, Medical Literature Analysis and Retrieval System Online, Índic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 55 publications
0
2
0
5
Order By: Relevance
“…Fatores como presença ou ausência de multimorbidades associadas, manutenção de relacionamentos e interações sociais, sentimentos positivos e esperançosos, além das facilidades e entraves no acesso ao serviço de saúde e de apoio especializado e apoio familiar favorem a QV da pessoa estomizada (FERNANDES COSTA et al, 2017). Além da capacidade individual de enfrentamento e superação atrelada a uma rede de apoio social ativa, favorece uma melhor adaptação e menos ocorrência de solidão, especialmente quando há convívio com pessoas em situação semelhante (MARQUES et al, 2016).…”
Section: Resultsunclassified
“…Fatores como presença ou ausência de multimorbidades associadas, manutenção de relacionamentos e interações sociais, sentimentos positivos e esperançosos, além das facilidades e entraves no acesso ao serviço de saúde e de apoio especializado e apoio familiar favorem a QV da pessoa estomizada (FERNANDES COSTA et al, 2017). Além da capacidade individual de enfrentamento e superação atrelada a uma rede de apoio social ativa, favorece uma melhor adaptação e menos ocorrência de solidão, especialmente quando há convívio com pessoas em situação semelhante (MARQUES et al, 2016).…”
Section: Resultsunclassified
“…When considering that the body image can be understood as an image that involves psychological, sociological, and physiological aspects that each individual forms of him/herself, NANDA ratifies the diagnosis "body dysmorphic disorder", defining it as a "confusion in the mental image of the physical self " (12) . This diagnosis may be related to ostomized people or to some real change in body structure (25) .…”
Section: Discussionmentioning
confidence: 99%
“…Integrative review 22 regarding the defining characteristics of body image disorder showed the significant presence of body image disorder in people with stomies, especially in women. The main changes observed in the literature were the actual change in the structure (100%), reports of perceptions that reflect an altered vision in the body's appearance (88.4%)…”
Section: Strongly Agreementioning
confidence: 99%